Child development surveillance: intervention study with nurses of the Family Health Strategy - Altamira Pereira da Silva Reichert; Neusa Collet; Sophie Helena Eickmann; Marília de Carvalho Lima (Universidade de São Paulo, 2015)
Objective: to evaluate the effectiveness of an educational action in child development surveillance performed by nurses working in primary health care.Methods: interventional study with a before-and-after type of design, carried out with 45 nurses and 450 mothers of children under 2 years of age. Initially, it was evaluated the practices and knowledge of nurses on child development surveillance and the mothers were interviewed about these practices. Subsequently, workshops were carried out with nurses and four months later, the knowledge of nurses and the maternal information were reevaluated.Results: after intervention there was significant increase in the frequency of the following aspects: from 73% to 100%, in relation to the practice of nurses of asking the opinion of mothers about their children's development; from 42% to 91%, regarding the use of the systematized instrument of evaluation; from 91% to 100% with respect to guidance to mothers on how to stimulate child development.Conclusions: the intervention contributed to the increase of knowledge of nurses and implementation of child development surveillance, showing the importance of this initiative to improve the quality of child health care.